Physical therapy using robotics: A project-based learning experience for undergraduate students - Lopez-Caudana, Edgar; López-Orozco, Christian Fernando; Mendoza Bárbara, César; Baltazar Reyes, Germán Eduardo; Ponce, Pedro; Chong-Quero, J. Enrique (Australasian Journal of Educational Technology, 2021)
The dynamic society we live in requires constant adaptation and innovation on every aspect of our daily lives, allowing us to improve the necessities of different people by doing it. For this study, we used a new approach with project-based learning to go beyond the typical environment in higher education and bring solutions to real-life scenarios. The project was developed with undergraduate engineering students in collaboration with a rehabilitation institute in Mexico City to design a physical therapy routine using the NAO robot. It allowed interaction between young patients in real time and fostered empathy while developing a final usable product. The study measured the usability of the robotic platform during the rehabilitation sessions and the reproducibility of the project through Cronbach's alpha evaluation. The usability results show a higher interest in the project from both the patients and the medical staff involved while constructing the material needed to develop a product that matches the standards given by the rehabilitation institute. Implications for practice or policy: Therapists could change traditional approaches to caregiving while adopting new technological methodologies using robots. Higher education students could supplement their school curricula with real-case scenarios such as creating innovative therapy sessions for people with physical disabilities. Schools might need to collaborate with a wide range of institutions to provide technological solutions to real problems.